ONLINE INSURANCE EXISTENCE IN INDONESIA BASED ON ISLAMIC LEGAL PERSPECTIVE AS A PROTECTION OF SPIRITUAL RIGHTS - DISEMADI, HARI SUTRA; PRANANINGTYAS, PARAMITA (Jurisdictie: Jurnal Hukum dan Syariah, 2020)
Globalization era requires Indonesia to always use technology and information in improving economy. This also applies to insurance companies that have implemented technology and information. Conventional insurance has developed into online one that attracts Indonesian citizen. However, today new issue is about protecting the spiritual rights of consumers as well as the halal or haram of online insurance. Answering this problem, this research will use normative juridical (doctrinal) method that prioritizes primary legal material i.e. insurance laws, consumer protection laws, and other legal materials. This research shows the existence of online insurance in Indonesia which rapidly develops because it offers more conveniences compared to conventional one. In Islamic law, online insurance is allowed as long as it is in line with Islamic law principles in protecting consumers’ spiritual rights. The example of sharia principle is cooperation by paying tabarru’ funds, using tabarru’ and tijarah agreement, and sharing similar responsibility between one participant and others (ta’awun). The legal basis for insurance in Indonesia is contained in the 2014 Law Number 40 and MUI Fatwa Number 21/DSN-MUI/X/2001.Era globalisasi mengharuskan Indonesia untuk selalu memanfaatkan teknologi dan informasi dalam meningkatkan perekonomian. Ini berlaku pula pada perusahaan asuransi yang telah menerapkan teknologi dan informasi. Asuransi konvensional telah berkembang menjadi asuransi online yang banyak diminati masyarakat Indonesia. Namun, persoalan yang hangat dibicarakan saat ini mengenai perlindungan hak spiritual konsumen serta halal atau haramnya asuransi online. Untuk menjawab persoalan tersebut, penelitian ini menggunakan metode yuridis normatif (doktrinal) yang mengedepankan bahan hukum primer yaitu undang-undang perasuransian, undang-undang perlindungan konsumen, serta bahan hukum lain. Penelitian ini menunjukan eksistensi asuransi online di Indonesia telah mengalami perkembangan pesat karena memberikan kemudahan dibanding asuransi konvensional. Dalam hukum Islam, asuransi online pada dasarnya diperbolehkan dengan syarat tidak bertentangan dengan prinsip-prinsip hukum Islam dalam melindungi hak spiritual konsumen. Contohnya prinsip syariah tersebut seperti bekerja sama dengan cara masing-masing mengeluarkan dana tabarru’, menggunakan akad tabarru’ dan akad tijarah, dan saling menanggung risiko antara satu peserta dengan peserta lainnya (ta’awun). Dasar hukum mengenai asuransi di Indonesia terdapat dalam UU Nomor 40 Tahun 2014 dan Fatwa MUI Nomor: 21/DSN-MUI/X/2001.